A CONSIDERATION OF EASTWARD SPREAD OF THE SAMARRAN PHENOMENON IN THE LIGHT OF NEW EVIDENCE ALONG THE ZAGROS PIEDMONT. (December 2020) - Darabi, Hojjat
Abstract : The Samarran phenomenon has been under discussion since the early 20 th century. Over the past several decades, increasing evidence has indicated that it was geographically distributed in a very large area across the Near East. In this regard, the eastward spread of the Samarran phenomenon across the Iranian frontier was little known, because related finds had mostly been recovered in the 1960–70s. This article highlights the discovery of new evidence in the transitional zone that connects the Zagros highlands with the Mesopotamian lowlands. During recent surveys in the plains of Mehran, Meimak, Soumar and Sarpol-e Zahab, a number of sites were found. They yielded ceramics identical with those already reported from nearby late Samarran sites such as Chogha Mami, Songor A and Rihan I. Chronologically, surface materials indicate that these newly found Iranian sites should belong to the late phase of Samarran period, coinciding with the so-called Chogha Mami Transitional (CMT). As seen from the natural setting of the sites along streams, and due to the predominance of nomadic herders in this transitional zone, we may assume that transhumant herders played a role in the eastward spread of the late Samarran phenomenon via the river valleys and that the site's inhabitants might have been familiar with a primitive irrigation system. Furthermore, it is speculated that the cold dry climatic event of 8.2 kya might have resulted in an increased intensity of population in the lowlands. Nevertheless, the subsequent climatic optimum appears to have paved the way for the eastward spread of late Samarran/CMT elements. Regardless of what was the major trigger of such an expansion, however, intensive economic interactions of societies probably played a role in the very early sixth millennium B.C., when natural raw materials such as bitumen were imported from western/southwestern Iran to central/southern Mesopotamia.